2002
DOI: 10.1186/1471-2199-3-4
|View full text |Cite
|
Sign up to set email alerts
|

Natural antisense RNA inhibits the expression of BCMA, a tumour necrosis factor receptor homologue.

Abstract: Background: BCMA (B-cell maturation) belongs to the tumour necrosis factor receptor gene family, and is specifically expressed in mature B lymphocytes. Antisense BCMA RNA is produced by transcription from the same locus and has typical mRNA features, e.g, polyadenylation, splicing, Kozak consensus sequence and an ORF (p12). To investigate the function of antisense BCMA RNA, we expressed BCMA in cell lines, in the presence of antisense p12 or a mutant lacking the initiation ATG codon (p12-ATG).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Antisense BCMA RNA is transcribed from the same locus as BCMA and has typical mRNA features, e.g., polyadenylation, splicing, Kozak consensus sequence and an open reading frame encoding an experimentally proven 115 amino acid peptide: p12 protein [107]. Experimental data suggests that antisense BCMA inhibits the expression of BCMA protein, while it does not affect the expression level of BCMA mRNA.…”
Section: Regulatory Functions Of Lncrnas and Mrnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Antisense BCMA RNA is transcribed from the same locus as BCMA and has typical mRNA features, e.g., polyadenylation, splicing, Kozak consensus sequence and an open reading frame encoding an experimentally proven 115 amino acid peptide: p12 protein [107]. Experimental data suggests that antisense BCMA inhibits the expression of BCMA protein, while it does not affect the expression level of BCMA mRNA.…”
Section: Regulatory Functions Of Lncrnas and Mrnasmentioning
confidence: 99%
“…Experimental data suggests that antisense BCMA inhibits the expression of BCMA protein, while it does not affect the expression level of BCMA mRNA. The inhibition of BCMA expression is obtained through the action of the antisense RNA and not of the p12 protein, although the exact mechanism is not fully understood [107]. …”
Section: Regulatory Functions Of Lncrnas and Mrnasmentioning
confidence: 99%
“…Some studies had suggested that cis -NATs represent transcriptional noise [11,12], while others had reported supportive evidence for the function of various cis -NATs [13-16], especially in RNA editing [17], stability [18], and translation [19]. Growing evidence implicating a role of NATs in medical conditions, such as hypertension [20] and immune disorders [21], suggests a functional role for cis -NATs. However, it cannot be assumed that cis -NATs are as actively regulated as its sense counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…For example, duplex formation between sense and antisense RNAs in the nucleus can modulate mRNA alternative splicing, editing and transport345. Sense-antisense duplex formation in the cytoplasm can change sense mRNA stability and translation efficiency678910. It has also been suggested that some antisense transcripts bind to the corresponding DNA strand and recruit DNA methyltransferases or histone-modifying enzymes, thereby modulating sense gene expression111213.…”
mentioning
confidence: 99%